The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.eiar.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the substantive effectiveness of SEA: Towards a better understanding

Abstract: a b s t r a c t a r t i c l e i n f oEvaluating the substantive effectiveness of strategic environmental assessment (SEA) is vital in order to know to what extent the tool fulfills its purposes and produces expected results. However, the studies that have evaluated the substantive effectiveness of SEA produce varying outcomes as regards the tool's contribution to decision-making and have used a variety of approaches to appraise its effectiveness. The aim of this article is to discuss the theoretical concept of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 32 publications
1
42
0
7
Order By: Relevance
“…Whereas EIA is the evaluation of effects likely to arise from a major project (or action) significantly affecting the environment, SEA refers to the systematic process of the analysis of environmental effects on policies, plans and programmes. Several authors argue that planning institutions could use IA measures in an "effective" manner by better integrating environmental considerations into the decision-making process [1,2,4,26]. Nevertheless, studies have shown that IA procedures often have a relatively weak impact on planning decisions -several critical challenges are pinpointed.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas EIA is the evaluation of effects likely to arise from a major project (or action) significantly affecting the environment, SEA refers to the systematic process of the analysis of environmental effects on policies, plans and programmes. Several authors argue that planning institutions could use IA measures in an "effective" manner by better integrating environmental considerations into the decision-making process [1,2,4,26]. Nevertheless, studies have shown that IA procedures often have a relatively weak impact on planning decisions -several critical challenges are pinpointed.…”
Section: 3mentioning
confidence: 99%
“…One is related to the difficulties of guiding commercially oriented industry actors to deploy wind energy in specific zones, to consider excluding other zones, as environmental and commercial concerns such as wind speed can often collide [16]. For the SEA to be an effective mechanism, it is critical that it is applied by the planning institution in the decision-making process, thus having an effect on the final planning outcome [26,34].…”
Section: Sea Mechanismsmentioning
confidence: 99%
“…VAN DOREN et al, 2013); (SCHULTZ, 2012); (GACHECHILADZE-BOZHESKU; FISCHER, 2012); (LUNDBERG et al, 2010) Tabela 1 -Critérios para avaliação da efetividade do tiering (conclusão).…”
Section: Proposição De Critériosunclassified
“…As a result, the survey considers not only the analytical criteria (A-F), but also relevant case studies identified in the literature (Smith & Sheate 2001;Hanusch & Glasson 2008;Thérivel et al 2009;Slunge et al 2011;Van Doren et al 2013;Victor & Agamuthu 2013). The set of questions generated features an investigation of how policy actors consider their current role in SEA processes, and how they would eventually improve it.…”
Section: The Interviewsmentioning
confidence: 99%
“…The policy-making perspective on SEA collects several factors and aims, synthesised by van Doren et al (2013) with the achievement of performance and conformance. This approach outlines the goals of SEA capacity building in supporting decision-making processes, and refers to two criteria used to evaluate effectiveness in decision-making and policy-making (Alexander & Faludi 1989;Barrett & Fudge 1981;Faludi 2000;Mastop & Faludi 1997).…”
Section: Sea Capacity Building and Policy-makingmentioning
confidence: 99%